Konsep dan Implementasi Pemberdayaan Ekonomi Ummat Perspektif Dakwah Islamiyah (Studi kasus pasar Muamalah, Dinar dan Dirham, Baitulmal Wattwamwil) - Zulkarnain Lubis (Jurnal Syntax Transformation, 2023)
A religious society is a characteristic of the Indonesian nation. This is marked by the majority of the population being Muslim and the extraordinary number of places of worship, both mosques and prayer rooms. Likewise, educational facilities, Islamic educational institutions based on Islamic boarding schools, integrated Islamic schools, and Islamic campuses are mushrooming throughout the country. Islamic mass organizations also contributed to the da'wah of Islam in this country. In terms of the economy, Islamic da'wah provides many guidelines and examples, such as how to build markets, how to transact goods properly, how to use the medium of exchange, and even trade contracts have been fully regulated in sharia rules so that people are not trapped by rib wi jahiliyyah behavior, in meeting their needs. His well-known book, Our Great Ulama, discusses how human nature tries to make ends meet. Human hands are scattered (searching for everything), and everyone is equal. However, something already owned by someone may not be taken by another person, except through barter for goods of the same value. The concept of da'wah in the economic empowerment of the Ummah as a theory, ideas, and ideas are very appropriate and valuable because the method of da'wah with the media of empowering the Ummah is needed a problem indeed for the Ummah in general. The implementation of Ummah Economic Empowerment from an Islamic Da'wah Perspective, with an empirical, cultural, sociological approach, with a historical approach to empowering the Ummah's economy, is indeed the initial improvement made by the Prophet Muhammad Salallahu 'Alaihi Wasallam when he migrated to Medina, organized the economy from a usury-free system, built markets lawful, and teaches transactions according to religious law. The cultural approach based on research findings on people's behavior is indeed colored and attached to local wisdom, the habits of the community in general in certain areas, so that the psychological atmosphere of the community is also greatly influenced by these rights.